2015
DOI: 10.1111/trf.13233
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of biosimilar filgrastim with originator filgrastim for peripheral blood stem cell mobilization and engraftment in patients with multiple myeloma undergoing autologous stem cell transplantation

Abstract: Nivestim is as effective as Neupogen for PBSC mobilization; however, its use was associated with a delay in PLT recovery. A prospective study should be conducted to confirm our findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 7 publications
1
8
0
1
Order By: Relevance
“…Retrospective, single-center study comparing Hospira biosimilar filgrastim ( n = 60) with ref filgrastim ( n = 38) for autologous SCM in pts with MM [66]…”
Section: Biosimilar Filgrastim Phase III Clinical Datamentioning
confidence: 99%
“…Retrospective, single-center study comparing Hospira biosimilar filgrastim ( n = 60) with ref filgrastim ( n = 38) for autologous SCM in pts with MM [66]…”
Section: Biosimilar Filgrastim Phase III Clinical Datamentioning
confidence: 99%
“…Previous studies have shown that the use of biosimilar filgrastim offers cost savings with similar efficacy when compared to the innovator product 17,18 . These findings and the apparent lack of differences in activity or safety between the innovator and biosimilar filgrastim products 4,[8][9][10][11]15 support the use of biosimilar filgrastim in clinical practice.…”
Section: Discussionmentioning
confidence: 79%
“…The fact that no data were collected systematically beyond D6 does not allow concluding that a lower total dose of filgrastim administered in our patients explains the differences in the mean number of CD34+ cells harvested. Higher CD34+ cell yields have been reported in other studies with biosimilar filgrastim, 9,11,16 but whether this is due to differences in the filgrastim products, patient profiles, methods for CD34+ quantification, or institutional policies on PBPC mobilization and harvesting remains unclear.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…a troca do Remicade para o CT-P13 não trouxe resultados diferentes. Da mesma forma, um estudo na Polônia com 39 crianças demonstrou também que essa mesma troca foi segura e eficaz (Danese et al, Neupogen na mobilização de PBSCs, mas seu uso foi associado a um atraso na recuperação de plaquetas(Pham et al, 2015). CSF novo, de referência.…”
unclassified